Pengaruh Model Pembelajaran Flipped Classroom Pada Pembelajaran Menulis Karya Imiah Siswa Kelas XI dalam Upaya Meningkatkan Self Improvement di Era New Normal - Rahmawati, Ira; Triyadi, Slamet; Rosalina, Sinta (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this research is to determine the effect of the learning model applied, namely the flipped classroom learning model, on learning to write scientific papers in an effort to increase the self-improvement of class XI students. The author uses a quantitative approach with a quasi-experimental method. The research design used was the Pre-Experimental method in the form of "one group pretest-posttest". This research was conducted at SMAN 1 Jatisari by taking one class as the research sample, namely class XI MIPA 1, totaling 36 respondents from the 171 population of class XI MIPA at SMAN 1 Jatisari.There are three stages in this research, namely: pretest, treatment, and posttest. The pretest was carried out to determine students' ability to write scientific papers before receiving treatment. After carrying out the pretest, teaching treatment was given with a modern learning style/flipped learning (flipped classroom model) with teaching materials that had been prepared in the sample class. After being given treatment, the researchers then conducted a posttest to find out whether there was an influence in implementing the flipped classroom learning model in learning to write scientific papers in an effort to increase students' self-improvement. The research was processed using normality tests, homogeneity tests and hypothesis tests. The results of data analysis in the research prove that the posttest scores of experimental class students have an average score of (85.3). Then, the results of the paired sample t-test data show a significant number between the pretest and posttest values ​​with a significance value (2-tailed) P = 0.000, <0.05. which can be concluded that there is a difference in the average value before and after treatment. Based on the hypothesis testing criteria, it can be concluded that the use of the flipped classroom learning model in learning to write students' scientific papers is better and there is an increase in students' self-improvement. The results of the research show that using the flipped classroom learning model can influence learning to write scientific papers in increasing the self-improvement of class XI MIPA 1 students at SMAN 1 Jatisari.